Numerical Simulation Study of the Load Sharing of an Arched Micropile Group in the Tizicao High-Position Landslide, China. Issue 6 (October 2020) - Wang, Wenpei; Yin, Yueping; Li, Dehua; Meng, Minghui; Luo, Gang; Zhang, Zhihua
Abstract: This study presents a combined anti-sliding structural system of micropile groups, with an arched shape on the plane and cement paste between the micropiles, in the Tizicao high-position landslide study conducted in the Wenchuan seismic area, China. Improvements in the landslide's stability as a result of the embedded micropile groups alone and in combination with long prestressed anchor cables are studied using FD-SRM and FOS contour analysis methods, respectively. The soil arching effect and the load sharing of the arched micropile group are analyzed using the numerical simulation method. Findings show that the arching effect is due to arc-shaped arrangements of the micropile groups. The design scheme of the embedded micropile groups improves the stability of this kind of thickly layered, high-position landslide. Moreover, its construction is convenient and the mechanism is clear, making it a good engineering reference for the treatment of similar landslides. The improvement in the landslide's stability is even better than that achieved by the combination of micropile groups and long prestressed anchor cables. Furthermore, the arching effect of multiple rows of micropile groups is significant and can effectively block the movement of the sliding body. The load transfer involved in the micropile–soil interaction process is a new type of two-part load sharing pattern. The soil arching behind the micropile groups takes more than 80% of the total load. A tangential tension zone appeared along the top of the pile–group arc crown when the arch protruded upward, and a related structural performance design should be considered in the future.